1978
DOI: 10.1007/bf00421238
|View full text |Cite
|
Sign up to set email alerts
|

86Rb+ fluxes and K+-stimulated nitrophenyl phosphatase acitvity in the pancreatic islets of genetically diabetic mice (C57BL/KsJ-db/db)

Abstract: Fluxes of 86Rb+ and hydrolysis of p-nitrophenyl phosphate were measured in collagenase-isolated islets of diabetic C57BL/KsJ-db/db-mice and normal controls (C57BL/KsJ-+/+). Both types of islets accumulated Rb+ avidly, as originally reported for hand-dissected islets of non-inbred ob/ob-mice. KsJ-db/db-mouse islets showed enhanced accumulation of Rb+ and normal activity of K+-activated nitrophenyl phosphatase. D-glucose, 20 mmol/l, inhibited Rb+ efflux in normal islets but not in those from KsJ-db/db-mice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

1979
1979
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…Since db/db mice are markedly hyperglycemic, the notion that anion conductance is adversely affected by chronic glucose exposure is supported. However, K ATP channel activity was also abnormal in those mice (Berglund et al 1978) but was not altered in the current study. In other cell types such as hepatocytes, cell swelling induces changes in metabolic processing of glucose by inhibiting glycogenolysis and glycolysis (Haussinger & Lang 1991).…”
Section: Discussioncontrasting
confidence: 50%
“…Since db/db mice are markedly hyperglycemic, the notion that anion conductance is adversely affected by chronic glucose exposure is supported. However, K ATP channel activity was also abnormal in those mice (Berglund et al 1978) but was not altered in the current study. In other cell types such as hepatocytes, cell swelling induces changes in metabolic processing of glucose by inhibiting glycogenolysis and glycolysis (Haussinger & Lang 1991).…”
Section: Discussioncontrasting
confidence: 50%
“…The basal 86Rb+ outflow from db/db A preliminary account of the results in this paper was presented at a Symposium on 'Biophysical Aspects of the fl-Cell and Insulin Release' held at the University of East Anglia in September 1983. * Address for reprint requests. islets is abnormally low (Berglund et al 1979(Berglund et al , 1980 and 86Rb+ outflow rate is glucose insensitive (Berglund et al 1978;Berglund, 1981) in contrast with the glucose-induced inhibition observed in normal rat and mouse islets (Henquin, 1978;Boschero & Malaisse, 1979;Dawson, Croghan, Atwater & Rojas, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Islets from diabetic mice exhibit abnormal per¬ meabilities for both Rb+ (K+) and Cl' as well as defective responses of these permeabilities to glu¬ cose (Berglund et al 1978bBerglund 1981;. Electrophysiological re¬ cordings revealed disturbances of the membrane electric potential in ß-cells from KsJ-rfé/rfè-mice (Meissner & Schmidt 1976 (Asplund et al 1979).…”
Section: Discussionmentioning
confidence: 96%
“…In old Ks]-db/db-mice the 3H20-production per unit dry weight of tissue was diminished at both 3 and 20 mmol/1 glucose; the relative increase in glucose metabolism due to a rise in glucose concentration was not decreased. Disturbances in Rb+ and Cf-fluxes (Berglund et al 1978bBerglund 1981; as well as in basal phosphate efflux occur already in young KsJ-db/db-mouse islets. Therefore the ionic changes do not seem to be caused by gross alterations in the glycolytic flux but more probably reflect aberrations in the function of the ß-cell plasma membrane.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation